Comparison between Intravenous Iron and Oral Iron Treatment in Term of Efficacy in cases of Postpartum Anemia - Noor ul Amina, Fatima Rehman, Paras (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare intravenous iron and oral iron treatment in term of efficacy in cases of postpartum anemia. Material and methods: Between July 2021 to December 2021, total 90 patients of post-partum anemia having age 20-35 year either primi or multi paras were recruited for this randomized controlled trial. Place of study was Department of Obstetrics & Gynecology, Qazi Hussain Ahmed Medical Complex Nowshera Medical College. Efficacy between IV iron and oral iron was compared. Results: Total 90 cases of post-partum anemia was recruited for this study. Age of the cases was between 20-35 years with mean age 27.34 ± 4.88 years, in IV iron group (A) and oral iron group (B), mean age was 27.53 ±4.94 years and 27.16 ± 4.87 years respectively. Study group A (IV iron group) and group B (oral iron group) was compared in term of efficacy by applying chi-square test. After applying chi-square test, significantly (P = 0.034) high proportion of efficacy was noted in IV iron group as compared to oral iron group (37/82.22% vs 28/62.22%). Conclusion: Results of this study showed that IV iron therapy had significantly higher efficacy rate as compared to oral iron in cases of postpartum anemia. Most of the women were between 20-25 years. Primiparas had higher proportion and most of the women belonged to rural area.